ANALISIS USAHA AGROINDUSTRI TAHU DI KELURAHAN KEKALIK JAYA KOTA MATARAM - IDA AYU NOPIARI; THERESIA SUZANNA CATHARINA (GANEC SWARA, 2023)
The purpose of this research is to find out the profit earned by tofu agro-industry business in Kekalik Jaya Village, Mataram City and to find out the marketing channel for tofu agro-industry business in Kekalik Jaya Village, Mataram City. The research method used is descriptive method, namely a method that focuses on solving existing problems by collecting data, compiling, analyzing, explaining and drawing conclusions. Determination of the sample using purposive sampling on the consideration that there are 227 tofu agro-industry entrepreneurs located in Kekalik Jaya Village. Respondents in this study were tofu agro-industry entrepreneurs who were taken randomly by taking 18 tofu agro-industry entrepreneurs in Kekalik Jaya Village.The results showed that the amount of revenue earned from the tofu agro-industry business in Kekalik Jaya Village, Mataram City was Rp. 3,692,500.00 per production, the total cost required for the tofu agro-industry business in the Kekalik Jaya sub-district, Mataram City, is Rp. Rp. 936,231.11 per production and the amount of profit earned by the tofu agro-industry in Kekalik Jaya Village, Mataram City is Rp. 2,756,268.89 per production. In this study there were only 14 retailers, so it can be illustrated that tofu marketing reaches consumers only through 2 marketing channels for tofu production. The link in the marketing channel shows that the marketing agency chain through which tofu agro-industry products pass is a direct marketing channel and a one-level channel.